Keterkaitan Motivasi dan Kecerdasan Emosional Terhadap Prestasi Belajar Siswa - Irna Kumala (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
It is obvious that Indonesia’s education must always be improved from year to year as a provision for Indonesia to compete in this globalization era. Related to technological era, students are more often access their gadgets at any time, this has a good impact but otherwise also have a bad impact on their academic achievement. Students become more infatuated with their gadgets that provide the latest things at any time. This decrease students' learning motivation greatly, and without sufficient emotional intelligence, their academic achievement are also affected. Thus the purpose of this study is to relate the motivation and emotional intelligence of students with their academic achievement. The relevant methods used are correlation and regression analysis. Primary data was collected by distributing questionnaires to 40 samples randomly. The results showed there was a very significant relationship between motivation and emotional intelligence on academic achievement, with F count of 48.081 and Sig. 0.00 < 0.05. Meanwhile, motivation has also significant relationship with academic achievement as evidenced by t count 2,940 which is greater than t table = 1.68 and Sig. 0.006 < 0.05. Then, emotional intelligence is also significant which is indicated by t count = 5.336 which is greater than t table = 1.68 and Sig. 0.00 < 0.05